Keberhasilan Inseminasi Buatan Pada Program Sapi dan Kerbau Komoditas Andalan Negeri (SIKOMANDAN) Berdasarkan Peran Peternak dan Inseminator: The Success of Artificial Insemination in the National Mainstay Commodity Cattle and Buffalo Program (SIKOMANDAN) Based on the Role of Farmers and Inseminators - Widiyaningsih, Putri Kartika; Iskandar, Faruq; Zulfanita, Zulfanita (Jurnal Riset Agribisnis dan Peternakan, 2023)
The SIKOMANDAN program is a government program to increase the population of cattle and buffalo in Indonesia. Artificial insemination is one of the work programs implemented in SIKOMANDAN. This study aims to determine the profile and role of inseminators and cattle farmers in the success of artificial insemination in the SIKOMANDAN program in Jogoresan Village. The population of this study was 142 cattle farmers. The research sample amounted to 60 farmers and 2 inseminators. Sampling used the Slovin formula with an error rate of 10%. Data collection instruments used questionnaires and Likert scales. Data analysis was descriptive and used SPSS Version 20 correlation test. The results of data analysis showed that inseminator factors in the form of work experience, distance traveled, thoroughness of procedures, and sanitation had a high role with a score of 4.3 and had a significant correlation (P < 0.05). Breeder factors in the form of knowledge of signs of lambing, IB time, and lambing cycle also have a high role with a Likert scale score of 4.0 and a significant correlation (P < 0.05).